THE ROLE AND SIGNIFICANCE OF "ARCHITECTURAL COMPOSITION AND DESIGN FUNDAMENTALS" IN THE EDUCATION OF FUTURE ARCHITECTS (American Journal of Technology and Applied Sciences, 2024)
This article provides information on "the role and importance of the science of architectural composition and design principles and the relevance of this science in the educational process" in the education of future architects.